Perbandingan Efektivitas Sayur Daun Katuk Dan Sayur Bayam Terhadap Peningkatan Produksi Asi Pada Ibu Nifas Di RSU Nurhayati Kabupaten Garut Tahun 2025 - Nurani, Ismi; Mardiyah, Maryam Syarah; Darmi, Salfia (Universitas Pahlawan Tuanku Tambusai, 2025)
Breast milk (ASI) plays an important role in the growth and development of infants. The coverage of exclusive breastfeeding in Garut Regency in 2022 reached 68.70%. Efforts that can be made by stimulating the production of prolactin and oxytocin hormones by providing katuk and spinach vegetables. The purpose of the study was to determine the effectiveness of katuk leaf vegetables and spinach on increasing breast milk production. The study used a qualitative design with a case study approach to 2 breastfeeding mothers who had little breast milk. The results of the study showed that for 7 days, giving katuk vegetables was effective in increasing breast milk production from 128 cc to 400 cc. Giving spinach was also effective in increasing breast milk production from 122 cc to 340 cc. In conclusion, there is a difference in effectiveness between giving katuk vegetables and spinach in increasing breast milk production where giving katuk vegetables is more effective than spinach with a difference in breast milk production of 54 cc. Suggestions, postpartum mothers can implement the use of katuk vegetables and spinach to help smooth breast milk production according to recommendations